Active Acoustics in Concert Halls – A New Approach - WOSZCZYK, Wieslaw (Archives of Acoustics, 2011)
Active acoustics offers potential benefits in music halls having acoustical shortcomingsand is a relatively inexpensive alternative to physical modifications of theenclosures. One critical benefit of active architecture is the controlled variability ofacoustics. Although many improvements have been made over the last 60 years inthe quality and usability of active acoustics, some problems still persist and theacceptance of this technology is advancing cautiously. McGill’s Virtual AcousticTechnology (VAT) offers new solutions in the key areas of performance by focusingon the electroacoustic coupling between the existing room acoustics and the simulationacoustics. All control parameters of the active acoustics are implemented inthe Space Builder engine by employing multichannel parallel mixing, routing, andprocessing. The virtual acoustic response is created using low-latency convolutionand a three-way temporal segmentation of the measured impulse responses. Thismethod facilitates a sooner release of the virtual room response and its radiationinto the surrounding space. Field tests are currently underway at McGill Universityinvolving performing musicians and the audience in order to fully assess andquantify the benefits of this new approach in active acoustics.